Orientation of Cultural Values of Javanese Ethnic as Migrant Contract Workers During Sugar Cane Harvest Period at PTPN I Regional 1 Kebun Bulu Cina, Deli Serdang Regency - Alristita Ardiawani; Sulian Ekomila; Supsiloani Supsiloani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the orientation of Javanese ethnic cultural values ​​in work ethics that can be seen from the activities and behavior of contract migrant workers while working at PTPN I Regional 1 Kebun Bulu Cina. The research method used in this study is a qualitative method with a descriptive approach. This research was conducted at PT Perkebunan Nusantara I Regional 1 Kebun Bulu Cina. The data collection techniques used were by conducting observations, direct interviews and documentation. The results of this study indicate that the Javanese ethnic group as contract migrant workers in carrying out their work are very oriented towards cultural values ​​such as ulet, persistence, responsibility, harmonious harmony, guyub rukun, obedience to superiors, friendly, polite, courteous and andhap ahsor or noble. The Javanese ethnic group as contract migrant workers has also become a transitional society that has an orientation towards the future.